Mapping of modifiable barriers and facilitators of medication adherence in bipolar disorder to the Theoretical Domains Framework: a systematic review protocol. Issue 2 (12th February 2019) - Prajapati, Asta Ratna; Dima, Alexandra Lelia; Clark, Allan B; Gant, Claire; Gibbons, Chris; Gorrod, Richard; Mosa, George; Scott, Sion; Song, Fujian; Teague, Bonnie; Twigg, Michael J; Wilson, Jon; et al.
Abstract : Introduction: People with bipolar disorder require long-term treatment but it is estimated that 40% of these people do not adhere to prescribed medication regimens. Non-adherence increases the risk of relapse, hospitalisation and suicide. Some evidence syntheses report barriers to mental health treatment adherence but rarely delineate between modifiable and non-modifiable barriers. They also fail to distinguish between the patients' perspective and that of other stakeholders such as clinicians despite of their different understanding and priorities about adherence. Facilitators of adherence, which are also important for informing adherence intervention design, are also lacking from syntheses and few syntheses focus on medications for bipolar disorder. This systematic review aims to identify modifiable barriers and facilitators (determinants) of medication adherence in bipolar disorder. We also plan to report determinants of medication adherence from perspectives of patients, carers, healthcare professionals and other third parties. A unique feature of this systematic review in the context of mental health is the use of the Theoretical Domains Framework (TDF) to organise the literature identified determinants of medication adherence. Methods and analysis: The protocol adheres to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols and ENhancing Transparency in REporting the synthesis of Qualitative research (ENTREQ) guidelines. This review will include both qualitative and quantitative primary studies exploring determinants of medication adherence in bipolar disorder. We will search the following databases using a preplanned strategy: CINAHL, Cochrane Library (CENTRAL), Embase, LiLACS, Medline, PsychINFO, PubMed without date restrictions. We will report the quality of included studies. We will use framework synthesis using the TDF as an a priori 'framework'. We will map the literature identified modifiable determinants to the domains of TDF. Ethics and dissemination: Ethical approval is not required as primary data will not be collected. The results will be disseminated through a peer-reviewed publication. PROSPERO registration number: CRD42018096306.